MONITORING AND ANALYSIS OF ROOM-AND-PILLAR MINING WITH CONTINUOUS MINER IN ESTONIAN OIL SHALE MINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
In this paper, the modeling, analysis and monitoring of a room-and-pillar mining technology in an Estonian underground mines is presented. Technology is based on continuous miner as the primary production machine. Many technical and economic parameters o f production, including loss of useful minerals, depend on a correct choice of the sizes for these elements. Without the account o f reological properties o f covered rocks, in particular the character of change o f their long strength, the account of the sizes of rooms and pillars on a certain determined term is impossible. For the modeling, the existing room- and-pillars determination method by IMS and with formulas by V. Undusk, Visual Basic for Application in Excel, Maplnfo, and Fast Lagrangian Analysis of Continua was used. Model allows determining the parameters of spontaneous collapse of the pillars and\ surface subsidence, optimized the working parameters for continuous mining. Proposed method suits for stability analysis, failure prognosis and monitoring.